2000
DOI: 10.1016/s1010-7940(00)00578-9
|View full text |Cite
|
Sign up to set email alerts
|

Congenital cystic adenomatoid malformation in an adult presenting as lung abscess

Abstract: The case of a 21-year-old male with congenital cystic adenomatoid malformation is presented. His medical history started after his birth with recurrent pulmonary infections during his infancy. Lung abscess of the right lower lobe was suspected and right lower lobectomy was performed to remove a sizeable mass infiltrating the largest part of the lobe. The clinical features, diagnostic procedures, differential diagnosis, pathologic characteristics, therapeutic assessment, etiopathology and prognosis of the tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 9 publications
0
22
0
2
Order By: Relevance
“…Up to 71% of such cases are asymptomatic at birth, and spontaneous regression has been reported in as many as 76% of cases without prenatal intervention5; approximately 85% of cases are diagnosed in the first 2 years of life and presentation is only rarely delayed until adulthood, as in our patient6. Although almost cases of CCAM are without symptoms and found incidentally, a few cases have dyspnea, hemoptysis, spontaneous pneumothorax, recurrent respiratory tract infections, pneumonia or lung abscesses7. The present patient had had a chronic cough for 10 months, and blood-tinged sputum.…”
Section: Discussionmentioning
confidence: 57%
“…Up to 71% of such cases are asymptomatic at birth, and spontaneous regression has been reported in as many as 76% of cases without prenatal intervention5; approximately 85% of cases are diagnosed in the first 2 years of life and presentation is only rarely delayed until adulthood, as in our patient6. Although almost cases of CCAM are without symptoms and found incidentally, a few cases have dyspnea, hemoptysis, spontaneous pneumothorax, recurrent respiratory tract infections, pneumonia or lung abscesses7. The present patient had had a chronic cough for 10 months, and blood-tinged sputum.…”
Section: Discussionmentioning
confidence: 57%
“…Hence, the emerging consensus is that imaging findings should simply be described, without attempting to make a pathological diagnosis on radiology. [13]…”
Section: Discussionmentioning
confidence: 99%
“…Type 1 is associated with the best overall prognosis and may remain undetected until later in life, as in the present case. The common clinical presentation of late-onset CCAM varies from an incidental finding to dyspnea, hemoptysis, pneumothorax, recurrent respiratory tract infections, pneumonia, and lung abscess [6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…However, other reports have indicated that many cases of CCAM resolve partially or completely in late gestation. These children may have persistent abnormalities that are subtle on radiography and thereby remain asymptomatic and undetected [10]. The differential diagnosis encompasses other congenital lung cysts with interrelated abnormalities including congenital lobar emphysema (CLE), bronchogenic cyst and pulmonary sequestration [3], obstructive emphysema caused by foreign-body aspiration, mucus plugs, tumors, and postinfectious lobar emphysema [11].…”
Section: Discussionmentioning
confidence: 99%